Evaluation of seed dressing chemicals for the management of sucking pests in summer groundnut (Arachis hypogaea L.): EVALUATION OF SEED DRESSING CHEMICALS FOR SUCKING PESTS IN SUMMER GROUNDNUT - D V KHANPARA; G M PARMAR; R M VIKANI; K L DOBARIYA (Journal of Oilseeds Research, 2017)
Field experiments were conducted during summer seasons of 2009-11 to determine the effectiveness of seed treatment with imidacloprid 600 FS @ 2 ml/kg seed, imidacloprid 600 FS @ 4 ml/kg seed, thiamethoxam 70 WS @ 1 g/kg seed, thiamethoxam 70 WS @ 2 g/kg seed, acetamiprid 20 SP @ 2 g/kg seed and carbosulfan 25 DS @ 5 g/kg seed against jassids and thrips in groundnut. Results indicated that significantly lowest population of jassids and thrips was recorded in the treatment of imidacloprid 600 FS @ 4 ml/kg seed and thiamethoxam70 WS @ 2 g/kg seed, respectively. The highest pod yield was recorded from imidacloprid 600 FS @ 4 ml/kg seed (1962 kg/ha) followed by imidacloprid 600 FS @ 2 ml/kg seed (1947 kg/ha), thiamethoxam 70 WS @ 2 g/kg seed (1917 kg/ha) and thiamethoxam 70 WS @ 1 g/kg seed (1897 kg/h). The highest incremental cost benefit ratio (1: 8.76) was observed in imidacloprid 600 FS @ 2 ml/kg seed followed by imidacloprid 600 FS @ 4 ml/kg (1: 5.47), thiamethoxam 70 WS @ 1 g/kg seed (1:4.13) and thiamethoxam 70 WS @ 2 g/kg seed (1:2.60). Based on the efficacyand economics, the study suggests that seed treatment with imidacloprid 600 FS @ 2ml/kg or thiamethoxam 70 WS @ 1 g/kg seed can be opted for inclusion in IPM programme against the sucking pests in groundnut.